Character Education Management in SMA Kakaskasen Seminary Catholic and SMA Lokon St. Nikolaus Tomohon - Marthinus M. Lintong; Joulanda AM Rawis; Johanis F. Senduk; Jeffry SJ Lengkong (Asia Pacific Journal of Management and Education (APJME), 2021)
Character education in Indonesia has been a crucial issue for more than two last decades. It has become the state priority in the national education policy for its character education reinforcement programs. This study aims to investigate the character education management in SMA Catholic Seminary Kakaskasen and SMA Lokon St. Nikolaus Tomohon. This is a multi-site study to examine and describe the planning (designing), actualization (implementation), and evaluating and monitoring procedures of their character education model. This study applied a descriptive qualitative approach. The findings indicate effective measures to manage their character education programs.